2016
DOI: 10.1007/s00068-016-0737-7
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic diaphragmatic rupture in pediatric age: review of the literature

Abstract: Purpose Despite a rising incidence in proximal humeral fractures, there is still no evidence for the best treatment option, especially for elderly patients. The aim of this retrospective cohort study was to evaluate health-related quality of life (HRQoL), functional outcome, pain and social participation in elderly patients, after operative and nonoperative treatment of displaced 3-and 4-part proximal humeral fractures. Methods 150 patients aged ≥ 65, treated for a displaced 3-or 4-part proximal humeral fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 79 publications
(41 reference statements)
0
8
0
1
Order By: Relevance
“…Marzona et al found that respiratory concerns are the most common presenting issue in both pediatric and adult patients. Additionally, gastrointestinal symptoms, if present, are more commonly found in adults [ 7 ]. This is particularly interesting as our patient was a 15-year-old female who presented with symptoms more likely found in an adult with TDH [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Marzona et al found that respiratory concerns are the most common presenting issue in both pediatric and adult patients. Additionally, gastrointestinal symptoms, if present, are more commonly found in adults [ 7 ]. This is particularly interesting as our patient was a 15-year-old female who presented with symptoms more likely found in an adult with TDH [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is considered that only 25-50% of traumatic lesions of the diaphragm are diagnosed by initial chest radiography [4]. According to reports, this method allows the detection of pathognomonic or suggestive signs in 70-85% of cases, while CT of the chest and abdomen confirms the diagnosis, with a sensitivity of up to 82% and a specificity of 87% [8]. Radiological signs suggestive of HDT include: elevated hemidiaphragm, distorted and obscured diaphragmatic margins, presence of intestinal shadows or air levels above the diaphragm, pleural collection, pulmonary collapse, and contralateral displacement of mediastinum [1].…”
Section: клінічний випадокmentioning
confidence: 99%
“…The incidence of HDT ranging from 0.08% to 8% is reported in the literature, with mortality rates ranging from 16.6% to 33.3% [3]. The reduced frequency, the non-specificity of the symptoms, the clinical evolution with associated lesions causes multiple diagnostic difficulties in 50-70% of cases, a high index of suspicion being necessary [8]. Late manifestation of traumatic lesions of the diaphragm is studied more in adults than in children [4].…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic diaphragmatic rupture (TDR) in the presence of other injuries and owing to its rarity may be easily missed in children (1,2). When presentation is delayed, morbidity and mortality rates increase proportionately (1,2). TDR may mimic conditions such as pneumothorax and bowel obstruction.…”
Section: Introductionmentioning
confidence: 99%